Comment on "Climate and agricultural land use change impacts on streamflow in the upper midwestern United States" by Satish C. Gupta et al. Issue 7 (10th July 2016) - Schilling, Keith E.
Abstract: Increasing precipitation and land use/land cover (LU/LC) change have contributed to increasing streamflow and base flow in many Midwestern rivers but the relative importance of causal factors is open to debate. The dominant LULC change in the agricultural Midwest is the emergence of soybean production that occurred in the mid‐ to late‐20th Century that replaced many sod‐based rotations and increased total row crop area devoted to annual maize and soybean crops. Increasing precipitation may be a more important factor for increasing total discharge whereas LULC changes contributed more to base flow changes. Key Points: Increasing precipitation and LU/LC change contributed to increasing streamflow Row crop expansion in Midwest increased base flow in rivers Soybean area is useful surrogate to track LULC changes